Testing agents for prevention or reversal of type 1 diabetes in rodents. - Christian W Grant; Catherine M Moran-Paul; Shane K Duclos; Dennis L Guberski; Guillermo Arreaza-Rubín; Lisa M Spain (PLoS ONE)
We report the results of an independent laboratory's tests of novel agents to prevent or reverse type 1 diabetes (T1D) in the non-obese diabetic (NOD) mouse, BioBreeding diabetes prone (BBDP) rat, and multiple autoimmune disease prone (MAD) rat models. Methods were developed to better mimic human clinical trials, including: prescreening, randomization, blinding, and improved glycemic care of the animals. Agents were suggested by the research community in an open call for proposals, and selected for testing by an NIDDK appointed independent review panel. Agents selected for testing to prevent diabetes at later stages of progression in a rodent model were a STAT4 antagonist (DT22669), alpha1 anti-trypsin (Aralast NP), celastrol (a natural product with anti-inflammatory properties), and a Macrophage Inflammatory Factor inhibitor (ISO-092). Agents tested for reversal of established T1D in rodent models were: alpha1 anti-trypsin (Aralast NP), tolerogenic peptides (Tregitopes), and a long-acting formulation of GLP-1 (PGC-GLP-1). None of these agents were seen to prevent or reverse type 1 diabetes, while the positive control interventions were effective: anti-CD3 treatment provided disease reversal in the NOD mouse, dexamethasone prevented T1D induction in the MAD rat, and cyclosporin prevented T1D in the BBDP rat. For some tested agents, details of previous formulation, delivery, or dosing, as well as laboratory procedure, availability of reagents and experimental design, could have impacted our ability to confirm prior reports of efficacy in preclinical animal models. In addition, the testing protocols utilized here provided detection of effects in a range commonly used in placebo controlled clinical trials (for example, 50% effect size), and thus may have been underpowered to observe more limited effects. That said, we believe the results compiled here, showing good control and repeatability, confirm the feasibility of screening diverse test agents in an independent laboratory.